Beyond Bone Remodeling: Denosumab’s Multisystemic Benefits in Musculoskeletal Health, Metabolism, and Age-Related Diseases—A Narrative Review - Yi-Ting Hung; Wen-Tien Wu; Ru-Ping Lee; Ting-Kuo Yao; Kuang-Ting Yeh (Biomedicines)
Background: Denosumab, a receptor activator of nuclear factor kappa-Β ligand (RANKL) inhibitor, demonstrates therapeutic effects beyond traditional osteoporosis management through the RANK/RANKL/osteoprotegerin pathway. Methods: This narrative review analyzed 37 studies (2018–2024) examining denosumab’s broader physiological effects and clinical applications. Results: Long-term safety data spanning 10 years showed sustained fracture prevention efficacy with a favorable benefit/risk profile. Compared to bisphosphonates, denosumab demonstrated superior outcomes in bone mineral density improvement and fracture risk reduction, particularly in elderly and frail populations. It enhanced muscular function by improving appendicular lean mass and grip strength while reducing fall risk. The drug showed potential cardiovascular benefits through its effects on cardiac and smooth muscle function. Notably, denosumab use was associated with reduced Type II diabetes mellitus risk through improved glucose metabolism. Additionally, it demonstrated promise in osteoarthritis treatment by suppressing osteoclast activity and chondrocyte apoptosis. While there are multisystem benefits, vigilance is required regarding adverse events, including hypocalcemia, infection risk, cutaneous reactions, and osteonecrosis of the jaw. Conclusions: Denosumab exhibits potential benefits in bone and systemic metabolism. Further research is needed to fully understand its therapeutic potential beyond osteoporosis and optimize clinical applications across different populations.